MOTIVASI PETANI MELAKUKAN USAHATANI BUAH NAGA (DRAGON FRUIT) DI DUSUN TAMBAKREJO - Firly Annaza Ambarwati; Ketut Arnawa; Putu Sukanteri (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2019)
Hamlet Tambakrejo is majority of farmer has planted or performan are dragon fruit with hylocereus polyrhizus varieties, it’s pink a fruit with meat of red fruit. Farmer in halmet Tambakrejo not only planted in the farm but also planted in his yard. This research aims to determine: (1). Know motivasai farmers do Dragon Fruit farm. (2) Analyzing the income of farmers in the Hamlet Tambakrejo Dragon Fruit. (3) Knowing the shape of a Dragon Fruit marketing channels in the Hamlet Tambakrejo. Research was conducted on the dragon fruit farmers in the Hamlet Tambakrejo to determine the respondents using slovin with random sampling method. Analysis of data using descriptive quantitative.The results showed that: (1) The main motivation of farmers in the Hamlet Tambakrejo view of the favorable results, easy maintenance and are rarely attacked by pests and diseases. Farmer in Hamlet Tambakrejo can give family need, so from income can buy and add vehicle, renovation house, child school to hight school, and can go umra and hajj. (2) Dragon fruit farming income against the in the Hamlet Tambakrejo farming with an area average of 0,44ha earn revenue Rp67.885.947 in a single season. (3) The form marketing channels for farmers sell to the collectors. so that farmers can quickly receive money or crops.